2021
DOI: 10.3390/ijerph19010270
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Changes in the Frequency of Social Participation on All-Cause Mortality in Japanese Older Adults: A Nationwide Longitudinal Study

Abstract: Previous studies have shown that more frequent social participation was associated with a reduced risk of mortality. However, limited studies have explored the changes in the frequency of social participation in older adults. We investigated the impact of the changes in the frequency of social participation on all-cause mortality in Japanese older adults aged 60 years and older. The current study, conducted as a secondary analysis, was a retrospective cohort study using open available data. The participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…Initiation of social participation after the age of 60 years failed to reduce the mortality risk. 18 In the present study, we mainly focused on the impact of the social activity frequency on midand long-term overall survival, and confirmed that social participation was a strong protective factor of health and longevity…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Initiation of social participation after the age of 60 years failed to reduce the mortality risk. 18 In the present study, we mainly focused on the impact of the social activity frequency on midand long-term overall survival, and confirmed that social participation was a strong protective factor of health and longevity…”
Section: Discussionsupporting
confidence: 73%
“…Shimatani et al also explored the association between the change of the frequency in social participation and all-cause mortality for individuals aged ≥60 years in Japan; they found that continued or decreased frequency of social participation was associated with a decreased risk of all-cause mortality. Initiation of social participation after the age of 60 years failed to reduce the mortality risk 18. In the present study, we mainly focused on the impact of the social activity frequency on mid- and long-term overall survival, and confirmed that social participation was a strong protective factor of health and longevity for older people.…”
Section: Discussionsupporting
confidence: 59%
“…In a longitudinal study consisted of 2,240 older people aged 60 years and older, and subjects were categorized into none, initiated, decreased and continued pattern based on the changes in the frequency of social participation, Shimatani et al demonstrated that the continued or decreased pattern was associated with a decreased risk of all-cause mortality, particularly in male subjects. The authors also urged initiation of social participation at an earlier phase of life transition since the initiated pattern failed to show any benefit in reducing mortality risk ( 16 ). The results were inconsistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…To the author’s knowledge, most studies used information from baseline surveys and assumed the frequency of social participation remained unchanged during the follow-up ( 9 , 10 , 13 ). Only one study had assessed the impact of the changes in the frequency of social participation on all-cause mortality and indicated no significant health benefits of initiated social participation in later life ( 16 ). Therefore, among older people who never participate in social activity at baseline, it is largely unknown whether increased participation in social activity in later life is associated with reduced risk of health outcomes.…”
Section: Introductionmentioning
confidence: 99%